Sprawa belgijska w działalności politycznej księcia Adama Jerzego Czartoryskiego wobec Wielkiej Brytanii (1831-1833) - Żurawski vel Grajewski, Radosław (Acta Universitatis Lodziensis. Folia Historica, 1999)
From the very beginning of his emigration Prince Czartoryski paid his attention to the political game of powers concerning the Belgian crisis. The Conference of Ambassadors in London tried to find a peaceful solution of that problem, but at the end of 1831 an international tension around it still existed. The main aim of Czartoryski’s diplomacy was to convince Foreign Secretary - lord Henry Palmerston that Great Britain should not only support Belgium in her existence but also Poland in her right to political independence. In his memoirs and notes for the British government he maintained that in some way the European powers had provoked the November Uprising in Poland in 1830 by confirmation of the justice of the aims of Belgian revolution. He claimed that such a result was produced by the decision of powers not to interfere to rebuild by force the political order formerly existing by a virtue of the Treaty of Vienna but to find a just solution of the Belgian-Dutch quarrel on the Conference of Ambassadors in London. Czartoryski demanded the same for Poland. In the spring of 1832 he managed to introduce the Polish question to the parliamentary debates concerning the Russo-Dutch loan. Than supported by Robert Cutlar Fergusson - the political friend of Czartoryski, Whig and the member of Parliament, he continued his propaganda in the House of Commons in April, June and August. He also tried to win the British support for the idea of the formation of the Polish troops in the Belgian army. The suggestion of such a formation first had come from British ambassador in Brussels sir Robert Adair, who than give up that idea as soon as the political agreement with tsar Nicholas I - the most powerful ally of William I the king of Holland in his quarrel with Leopold I - the king of Belgium - seemed to be possible. Both - the Polish propaganda in British Parliament and the success of the attempts to create the Polish troops in Belgium depended on the co-operation of Foreign Office with the Polish émigrés. Palmerston was well informed and consulted by the Poles. He gave them some support in their activity, but only as far as it was in accordance with the British political aims. In fact the Polish question was for Foreign Office a kind of a tool to make a political pressure on the diplomacy of Russia, Prussia and Austria to bring them to the peacefully settlement of Belgian question according to the British will.